(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
Fiscal policy may promote growth and human development via a variety of routes. These channels encompass both macroeconomic (such as the impact of the budget deficit on GDP) and microeconomic factors (through its influence on the efficiency of resource use). The article deals with expressing the fiscal policy in the formation of budget revenues and issues of improvement, as well as some key features concerned with fiscal policy have been implemented